Pemberdayaan Berkelanjutan: Pengembangan Lahan Pertanian untuk Kemandirian Yayasan Griya Cendekia - Muhammad, Hasman Zhafiri; Al Munawwar, Muhammad Luthfi (Universitas Cokroaminoto Yogyakarta, 2025)
The Griya Cendekia Foundation is an organization primarily dedicated to advancing educational objectives. Despite this focus, the foundation faces economic constraints, lacking the financial independence necessary to sustain the daily operations. To address this challenge, the service team has leveraged the foundation’s underutilized assets—namely, vacant land—by converting it into productive agricultural land. This initiative aims to generate revenue to meet the operational demands of the Griya Cendekia Playen Foundation. The approach adopted for this intervention is Participatory Action Research (PAR), comprising four iterative stages: exploration (To Know), planning (To Plan), comprehension (To Understand), and implementation (To Act). These stages are systematically integrated into the service process, with the community positioned as active agents of change. The result of this effort is the creation of functional agricultural land that bolsters the economic viability of Griya Cendekia, effectively addressing the critical need for funding to support its core activities, including education, healthcare, and community development initiatives (in the form of KUB)